2014
DOI: 10.1001/jamaneurol.2014.1646
|View full text |Cite
|
Sign up to set email alerts
|

Midlife Hypertension and 20-Year Cognitive Change

Abstract: IMPORTANCE Hypertension is a treatable potential cause of cognitive decline and dementia, but its greatest influence on cognition may occur in middle age.OBJECTIVE To evaluate the association between midlife (48-67 years of age) hypertension and the 20-year change in cognitive performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
202
1
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 385 publications
(224 citation statements)
references
References 42 publications
14
202
1
7
Order By: Relevance
“…Higher midlife SBP levels have been consistently associated with lower cognitive function in later life 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11. Most studies have assessed cognitive function at a single time point,4, 5, 6, 7, 8, 9 and, thus, our results have extended our understanding of this relationship by taking cognitive decline into account.…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…Higher midlife SBP levels have been consistently associated with lower cognitive function in later life 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11. Most studies have assessed cognitive function at a single time point,4, 5, 6, 7, 8, 9 and, thus, our results have extended our understanding of this relationship by taking cognitive decline into account.…”
Section: Discussionsupporting
confidence: 60%
“…Therefore, characterization of individual DBP in midlife by a single measurement may be limited, and this might have contributed to the inconsistent results 5, 6, 8, 30. Indeed, a prior study from the ARIC Study demonstrated that higher DBP at visit 2 was associated with a steeper decline in global cognition from visit 2 to visit 5 11. The inconsistency may be attributable to the definition of DBP (ie, we defined DBP on the basis of 4 clinic BP measurements [from visit 1 to visit 4 BPs] over 9 years).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on observational data, an increase in BP of 20 mm Hg systolic or 10 mm Hg diastolic is associated with a doubling of the risk of CVD death, regardless of age 5. Further, hypertension in middle age is known to increase the risk of chronic kidney disease (CKD) and dementia in later life, an important issue given the aging demographic in Western societies 6. Finally, despite the fact that BP recognition and control are improving, it is concerning that nearly half of the hypertensive population remains suboptimally controlled 2…”
Section: Introductionmentioning
confidence: 99%